Proceedings of the 2016 Childhood Arthritis and Rheumatology Research Alliance (CARRA) Scientific Meeting. Issue 1 (July 2016) - Fotis, Lampros; Shaikh, Nur; Baszis, Kevin; French, Anthony; Tarr, Phillip; Grevich, Sriharsha; Lee, Peggy; Ringold, Sarah; Leroux, Brian; Leahey, Hannah; Yuasa, Megan; Foster, Jessica; et al.
Table of Contents P1 Serologic evidence of gut-driven systemic inflammation in juvenile idiopathic arthritis Lampros Fotis, Nur Shaikh, Kevin Baszis, Anthony French, Phillip Tarr P2 Oral health and anti-citrullinated peptide antibodies (ACPA) in juvenile idiopathic arthritis Sriharsha Grevich, Peggy Lee, Sarah Ringold, Brian Leroux, Hannah Leahey, Megan Yuasa, Jessica Foster, Jeremy Sokolove, Lauren Lahey, William Robinson, Joshua Newsom, Anne Stevens P3 Novel autoantigens for endothelial cell antibodies in pediatric rheumatic diseases identified by proteomics Rie Karasawa, Mayumi Tamaki, Megumi Tanaka, Toshiko Sato, Kazuo Yudoh, James N. Jarvis P4 Transcriptional profiling reveals monocyte signature associated with JIA patient poor response to methotrexate Halima Moncrieffe, Mark F. Bennett, Monica Tsoras, Lorie Luyrink, Huan Xu, Sampath Prahalad, Paula Morris, Jason Dare, Peter A. Nigrovic, Margalit Rosenkranz, Mara Becker, Kathleen M. O'Neil, Thomas Griffin, Daniel J. Lovell, Alexei A. Grom, Mario Medvedovic, Susan D. Thompson P5 A multi-dimensional genomic map for polyarticular juvenile idiopathic arthritis Lisha Zhu, Kaiyu Jiang, Laiping Wong, Michael J Buck, Yanmin Chen, Halima Moncrieffe, Laura Brungs, Tao Liu, Ting Wang, James N Jarvis P6 Tocilizumab for treatment of children with refractory JIA Khaled Alsaeid, Jasim Alfailakawi, Hamid Alenezi, Hazim Alsaeed P7 Clinical characteristics of the initial patients enrolled in the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Registry Tim Beukelman, Marc Natter, Norm Ilowite, Kelly Mieszkalski, Grendel Burrell, Brian Best, Helen Bristow, Shannon Carr, Anne Dennos, Rachel Kaufmann, Yukiko Kimura, Laura Schanberg P8 Comparative performance of small and large clinical centers in a comprehensive pediatric rheumatology disease registry Peter R Blier P9 Clinical characteristics of children with membranous lupus nephritis: The Childhood Arthritis and Rheumatology Research Alliance Legacy Registry Alexis Boneparth, Scott E. Wenderfer, L. Nandini Moorthy, Suhas M. Radhakrishna, Anna Carmela P. Sagcal-Gironella, Emily von Scheven P10 Rituximab use in pediatric lupus anticoagulant hypoprothrombinemia syndrome - a two center experience Kader Cetin Gedik, Salma Siddique, Cassyanne L. Aguiar, Doruk Erkan P11 Predictors of complementary and alternative medicine use and response in children with musculoskeletal conditions Ezra Cohen, Yvonne Lee, Michelle Dossett, Darshan Mehta, Roger Davis P12 Comparison of pediatric rheumatology and nephrology survey results for the treatment of refractory proliferative lupus nephritis and renal flare in juvenile SLE Mileka Gilbert, Beatrice Goilav, Esra Meidan, Joyce Hsu, Alexis Boneparth, Anabelle Chua, Stacy Ardoin, Scott E. Wenderfer, Emily Von Scheven, Natasha M. Ruth P13 Transitioning lupus patients from pediatric to adult rheumatology Joyce Hui-Yuen, Kader Cetin Gedik, Liza Bermudez, Ashlea Cook, Lisa Imundo, Amy Starr, Andrew Eichenfield, Anca Askanase P14 The systemic juvenile idiopathic arthritis cohort of the Childhood Arthritis & Rheumatology Research Alliance Registry Ginger Janow, Laura E. Schanberg, Soko Setoguchi, Victor Hasselblad, Elizabeth D. Mellins, Rayfel Schneider, Yukiko Kimura, The CARRA Legacy Registry Investigators P15 Results of the pilot study of the Childhood Arthritis and Rheumatology Research Alliance (CARRA) consensus treatment plans for new-onset systemic juvenile idiopathic arthritis Yukiko Kimura, Sriharsha Grevich, Timothy Beukelman, Esi Morgan, T Brent Graham, Maria Ibarra, Yonit Sterba Ruas, Marisa Klein-Gitelman, Karen Onel, Sampath Prahalad, Marilynn Punaro, Sarah Ringold, Dana Toib, Heather Van Mater, Jennifer E. Weiss, Pamela F. Weiss, Kelly Mieszkalski, Laura E. Schanberg P16 A systemic review of pain relief modalities in juvenile idiopathic arthritis: First step in developing a novel decision support intervention Timothy S. H. Kwok, Jacinthe Bisaillon, Christine Smith, Lucie Brosseau, Jennifer Stinson, Adam M. Huber, Ciaran M. Duffy, Karine Toupin April P17 Barriers and facilitators to care retention for pediatric systemic lupus erythematous patients in South Africa: A qualitative study Laura B Lewandowski, Christiaan Scott P18 Evaluating the feasibility of conducting comparative effectiveness studies in juvenile Localized Scleroderma (jLS) Suzanne C. Li, Kathryn S. Torok, C. Egla Rabinovich, Sandy D. Hong, Mara L Becker, Fatma Dedeoglu, Maria F. Ibarra, Polly J Ferguson, Rob C. Fuhbrigge, Katie G. Stewart, Elena Pope, Ronald M. Laxer, Thomas G. Mason, Gloria C. Higgins, Xiaohu Li, Marilynn G. Punaro, George Tomlinson, Eleanor Pullenayegum, John Matelski, Laura Schanberg, Brian M. Feldman P19 Tonsillar histology in patients with periodic fever, aphthous stomatitis, pharyngitis, adenitis (PFAPA) syndrome Kalpana Manthiram, Hernan Correa, Kathryn Edwards P20 Clinical course of juvenile dermatomyositis presenting as skin predominant disease Edward J. Oberle, Michelle Bayer, Dominic O. Co, Hatice Ezgi Baris, Yvonne Chiu, Adam Huber, Susan Kim P21 A Survey of musculoskeletal ultrasound practices of pediatric rheumatologists in North America Edward J Oberle, Timothy Beukelman P22 Assessment, classification and treatment of calcinosis as a complication of juvenile dermatomyositis: A survey of pediatric rheumatologists by the Childhood Arthritis and Rheumatology Research Alliance Amir B. Orandi, Kevin W. Baszis, Vikas Dharnidharka, Mark F. Hoeltzel, for the CARRA JDM Committee P23 CARRA dermatomyositis CTP pilot study Ann Reed, Adam Huber, George Tomlinson, Eleanor Pullenayegum, John Matelski, Y. Ingrid Goh, Laura Schanberg, Brian M. Feldman P24 Unexpectedly high incidences and prolonged disease activity in children with chronic non-bacterial osteomyelitis (CNO) as compared to bacterial osteomyelitis Anja Schnabel, Ursula Range, Gabriele Hahn, Timo Siepmann, Reinhard Berner, Christian Michael Hedrich P25 Juvenile systemic sclerosis cohort within the Childhood Arthritis and Rheumatology Research Alliance (CARRA) Legacy Registry: Follow up characteristics Brandi Stevens, Kathryn S. Torok, Suzanne Li, Nicole Hershey, Megan Curran, Gloria Higgins, Katharine Moore, Egla Rabinovich, Anne M. Stevens, for the CARRA Registry Investigators P26 Development and usability testing of an iPad and desktop psycho-educational game for children with Juvenile Idiopathic Arthritis and their parents Jennifer Stinson, Mark Connelly, Adam Huber, Nadia Luca, Lynn Spiegel, Argerie Tsimicalis, Stephanie Luca, Naweed Tajuddin, Roberta Berard, Julia Barsalou, Sarah Campillo, Paul Dancey, Ciaran Duffy, Brian Feldman, Nicole Johnson, Patrick McGrath, Natalie Shiff, Shirley Tse, Lori Tucker, Charles Victor P27iCanCope TM : User-centred design and development of a smartphone app to support self-management for youth with arthritis pain Jennifer Stinson, Chitra Lalloo, Lauren Harris, Joseph Cafazzo, Lynn Spiegel, Brian Feldman, Nadia Luca, Ronald Laxer P28 Accessing pediatric rheumatology care: Despite barriers, few parents prefer telemedicine Danielle R. Bullock, Richard K. Vehe, Lei Zhang, Colleen K. Correll1 P29 Exploration of factors contributing to time to achieve clinically inactive disease (CID) in juvenile idiopathic arthritis (JIA): A preliminary report Suhas Ganguli, Max Shenberger, Ritesh Korumilli, Beth Gottlieb P30 Pediatric rheumatology referral patterns: Presenting complaints of new patients at a large, urban academic center Martha Rodriguez, Deirdre de Ranieri, Karen Onel, Linda Wagner-Weiner, Melissa Tesher P31 Quality improvement (QI) initiatives in childhood systemic lupus erythematosus (cSLE) Elizabeth Roth Wojcicki, Kristyn L. Maletta, Dominic O. Co, Marsha Malloy, Sarah Thomson, Judyann C. Olson P32 Proliferative lupus nephritis in juvenile SLE: Support from the pediatric nephrology community for the definitions of responsiveness and flare in the 2012 consensus treatment plans Scott E. Wenderfer, Mileka Gilbert, Joyce Hsu, Sangeeta Sule, Tamar B. Rubinstein, Beatrice Goilav, Daryl M. Okamura, Annabelle Chua, Laurence A. Greenbaum, Jerome C. Lane, Emily von Scheven, Stacy P. Ardoin, Natasha M. Ruth P33 The steroid taper app: Making of a mobile app Jennifer M. P. Woo, Marsha M. Malloy, James A. Jegers, Dustin J. Hahn, Mary K. Hintermeyer, Stacey M. Martinetti, Gretchen R. Heckel, Elizabeth L. Roth-Wojcicki, Dominic O. Co